Development of a multiaxial fatigue damage parameter and life prediction methodology for non-proportional loading - Sandip Suman; Alan Kallmeye; John Smith (Fracture and Structural Integrity)
Most of the prior studies on the prediction of fatigue lives have been limited to uniaxial loading cases, whereas real world loading scenarios are often multiaxial, and the prediction of fatigue life based upon uniaxial fatigue properties may lead to inaccurate results. A detailed exploration of multiaxial fatigue under constant amplitude loading scenarios for a range of metal alloys has been performed in this study, and a new methodology for the accurate prediction of fatigue damage is proposed. A wide variety of uniaxial, torsional, proportional and non-proportional load-paths has been used to simulate complex, real-world loading scenarios. Test data have been analyzed and a critical-plane based fatigue damage parameter has been developed. This fatigue damage parameter contains stress and strain terms, as well as a term consisting of the maximum value of the product of normal and shear stresses on the critical plane. The shear-dominant crack initiation phenomenon and the combined effect of shear and tensile stresses on micro-crack propagation have been modeled in this work. The proposed formulation eliminates many of the shortcomings of the earlier developed critical-plane fatigue damage models. It is mathematically simple with substantially fewer material dependent constants, and provides design engineers with a tool to predict the fatigue life of machine parts with minimal computational effort. This life prediction methodology is intended for a wide variety of LCF and HCF loadings on machine parts made of metals including advanced alloys